2022
DOI: 10.1021/acs.jmedchem.1c01563
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted 5-(1H-Indol-2-yl)-2-methoxyanilines Are Allosteric Inhibitors of the Linoleate Oxygenase Activity of Selected Mammalian ALOX15 Orthologs: Mechanism of Action

Abstract: Here, we describe the first systematic study on the mechanism of substrate-selective inhibition of mammalian ALOX15 orthologs. For this purpose, we prepared a series of N-substituted 5-(1H-indol-2-yl)­anilines and found that (N-(5-(1H-indol-2-yl)-2-methoxyphenyl)­sulfamoyl)­carbamates and their monofluorinated analogues are potent and selective inhibitors of the linoleate oxygenase activity of rabbit and human ALOX15. Introduction of a 2-methoxyaniline moiety into the core pharmacophore plays a crucial role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…To test the validity of our hypothesis, the octyl (N-(5-(1 H -indol-2-yl)-2-methoxyphenyl)sulfamoyl)carbamate ( 1 ) was prepared according to the procedure we described previously [ 27 ]. N-(2-(5-(4-methoxyphenyl)-2-(pyridin-2-yl)-1 H -imidazol-4-yl)ethyl)-4-pentylbenzenesulfonamide ( 2 ) was synthesized from 4-chloro-1-(4-methoxyphenyl)butan-1-one ( 4 ) according to Weinstein et al [ 21 ], following a slightly modified synthetic protocol (see Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To test the validity of our hypothesis, the octyl (N-(5-(1 H -indol-2-yl)-2-methoxyphenyl)sulfamoyl)carbamate ( 1 ) was prepared according to the procedure we described previously [ 27 ]. N-(2-(5-(4-methoxyphenyl)-2-(pyridin-2-yl)-1 H -imidazol-4-yl)ethyl)-4-pentylbenzenesulfonamide ( 2 ) was synthesized from 4-chloro-1-(4-methoxyphenyl)butan-1-one ( 4 ) according to Weinstein et al [ 21 ], following a slightly modified synthetic protocol (see Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…This result suggested that the pocket of monomer A needs structural rearrangement to accommodate compound 2 in the substrate-binding pocket. For this reason, additional docking calculations were carried out with compound 2 using the binding cavity of monomer A, once adapted to accommodate compound 1 [ 27 ]. In this reorganized structure of the protein, several binding modes of compound 2 were found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a typical cut-off value for studies with MD simulations followed by MM/GBSA calculations. 21,22,[69][70][71][72][73][74] SHAKE algorithm was used to constrain bonds with hydrogen atoms, enabling the application of an integration time-step of 2 fs.…”
Section: Molecular Dynamicsmentioning
confidence: 99%